A new method of bonding an attachment to an impacted tooth - Gupta, Sanjay Prasad; Dutta, Kishor; Rauniyar, Shristi (Orthodontic Journal of Nepal, 2023)
Orthodontic traction of impacted tooth requires surgical exposure followed by bonding an attachment on the exposed impacted tooth. In the past, various methods of attachment have been used for bonding an attachment. However, various problems like failure of bonding or tearing of mucosa due to prominent attachment have remained consistent. This proposed new attachment technique is simple and inexpensive that reduce the bond failure rates and discomfort to the patient during orthodontic traction.